Peripheral Nerve Regeneration From Surgery to New Therapeutic Approaches Including Biomaterials and Cell-Based Therapies Development - Colette Mauricio, Ana (IntechOpen, 2017)
Peripheral nerve injuries are a high-incidence clinical problem that greatly affects patients' quality of life. Despite continuous refinement of microsurgery techniques, peripheral nerve repair still stands as one of the most challenging tasks in neurosurgery, as functional neuromuscular recovery is rarely satisfactory in these patients. Therefore, the improvement of surgical techniques and the clinical application of innovative therapies have been intensively studied worldwide. Direct nerve repair with epineural end-to-end sutures is still the gold standard treatment for severe neurotmesis injuries but only in cases where well-vascularized tension-free coaptation can be achieved. When peripheral nerve injury originates a significant gap between the nerve stumps, nerve grafts are required, with several associated disadvantages. Therefore, the development of scaffolds by tissue engineering can provide efficient treatment alternatives to stimulate optimum clinical outcome. Nerve conduit tailoring involves reaching ideal wall pores, using electrospinning techniques in their fabrication, surface coating with extracellular matrix materials, and adding of growth factors or cell-based therapies, among other possibilities. Also, intraluminal cues are employed such as the filling with hydrogels, inner surface modification, topographical design, and the introduction of neurotrophic factors, antibiotics, anti-inflammatories and other pharmacological agents. A comprehensive state of the art of surgical techniques, tissue-engineered nerve graft scaffolds, and their application in nerve regeneration, the advances in peripheral nerve repair and future perspectives will be discussed, including surgeons' and researchers' own large experience in this field of knowledge.